Pelatihan Media Audio - Visual dalam Meningkatkan Kemampuan Berbicara Bahasa Inggris Bagi Guru Majdah Al - Fayyadh Islamic School - Akmal Akmal; Indra Ramadona Harahap; Zulkarnain Sirait (Smart Education, 2021)
Abstract: Audio-visual media is a method to produce or deliver materials by using mechanical and electronic machines to present audio-visual messages. Teaching through audiovisual media is clearly characterized by the use of hardware during learning such as television, tape recorder, and wide visual projector. In this English-speaking learning using video media, infocus, and laptop. The material is given in the form of overall English. The researcher presented several films about English and the English Speaking Club for Students students were very passionate and responded positively so that they were able to speak in English by communicating entirely in English. They are also more interactive in speaking English. The students’ speaking ability got the progress so significant and can improve their speaking skills in English. Keywords: Audio-visual; Media; Speaking Skill. Abstrak: Media audio visual adalah suatu cara untuk menghasilkan atau menyampaikan materi dengan menggunakan mesin mekanik dan elektronik untuk menyajikan pesan audio visual. Pengajaran melalui media audiovisual jelas ditandai dengan penggunaan perangkat keras selama pembelajaran seperti televisi, tape recorder, dan proyektor visual yang lebar. Dalam pembelajaran berbahasa Inggris ini menggunakan media video, infocus, dan laptop. Materi yang diberikan berupa bahasa Inggris secara keseluruhan. Peneliti menyajikan beberapa film tentang Bahasa Inggris dan English Speaking Club untuk Siswa siswa sangat antusias dan merespon positif sehingga mereka mampu berbicara dalam bahasa Inggris dengan berkomunikasi sepenuhnya dalam bahasa Inggris. Mereka juga lebih interaktif dalam berbicara bahasa Inggris. Kemampuan berbicara siswa mengalami kemajuan yang sangat signifikan dan dapat meningkatkan keterampilan berbicara mereka dalam bahasa Inggris. Kata Kunci: Audio-visual; Media; Kemampuan berbicara.